Risky sexual practice and associated factors among street children of Wonago town, Gedeo zone, Southern Ethiopia - Zenebe, Getachew Assefa; Alemu, Wagaye; Muche, Temesgen; Debela, Berhanu Gidisa (Frontiers in Public Health, 2023)
Introduction A “risky sexual practice” is any sexual act that might put an individual’s social, physical, and psychological health at risk and increase the likelihood of adverse sexual and reproductive health consequences. Street children have risky sexual practices, which place them at all kinds of health risks. Therefore, the aim of this study is to assess risky sexual practices and associated factors among street children in Wonago Town, southern Ethiopia. Methods A community-based cross-sectional study design was employed. About 214 street children, aged 10–18, residing in Wonago Town from September 1–30, 2021, participated in the study. Data was gathered from all of the street children in Wonago town. A pre-tested and structured interviewer-administered questionnaire was used to collect data. Epi data software was used to enter the collected data, which was then exported to SPSS for analysis. A logistic regression model was applied to identify the associated factors. A p value <0.05 was used to declare the significant variables. Results A total of 214 street children were involved in the study. Overall, the magnitude of risky sexual practices was 43.46 percent (95% CI: 38.3–48.62). About 52.7% of participants had ever had sexual intercourse in the last year, and of them, around 43.5% had more than one sexual partner. Among sexually active street children, 40.9% never used a condom during sexual intercourse. Age (Adjusted Odd Ratio (AOR): 1.42, 95%CI: 1.03–2.37), educational status (AOR: 5.73, 95%CI: 1.49–10.51), substance use (AOR: 1.24, 95%CI: 1.03–2.07), duration on the street (AOR: 2.14, 95%CI: 1.03–4.12), and daily income (AOR: 0.68, 95%CI: 0.32–0.98) were found to be significantly associated with risky sexual practices. Conclusion Risky sexual practices among street children were more prevalent in Wonago Town, Southern Ethiopia. Children’s age, educational status, daily income, duration on the street, and status of substance use were the factors that contributed to risky sexual practices. As a result, conducting information and education campaigns, developing income-generating activities for children, increasing children’s school enrollment and attendance, improving access to sexual and reproductive health services, and providing capacity-building training for health care providers may all help to reduce risky sexual practices.